APPLICATION OF SPACE MAKERSPACES IN BATUSANGKAR IAIN LIBRARY: LIBRARY DEVELOPMENT STRATEGY - Tri Yuliani (IAIN Batusangkar, 2020)
In this paper, we describe the maker concept, movement and culture and its impact on and relationship with libraries. We provide a comprehensive review of library makerspaces in IAIN Batusangkar supported by several case studies. We intend this review to be used as a reference resource or tool for libraries planning to implement a new makerspace.